Diversidade genética, demografia histórica e aspectos sócio-reprodutivos do mico-leão-preto (Leontopithecus chrysopygus) - Javarotti, Nathalia Bulhões (Universidade Federal de São Carlos, 2024)
Changes in the landscape, caused by habitat loss and fragmentation due to deforestation, have been posing a great challenge for the survival and persistence of forest-dependent species. The Neotropical primates are among the animal species most threatened by such changes. Among them is the black lion tamarin (BLT), Leontopithecus chrysopygus, which is endemic to the Atlantic Forest of the state of São Paulo, a biome with intense reduction of forest cover. Currently, the distribution of this species is limited to about 20 forest fragments, comprised in three regions along the Paranapanema river, which present landscape diversity in terms of size, resources and connectivity. Fragmented, disconnected and low-density populations tend to be more susceptible to events that promote genetic diversity reduction and inbreeding increase, such as, for example, absence or decrease of gene flow, and increase of genetic structure and drift. In this context, such populations are more likely to suffer local extinctions, compromising the maintenance and viability of the species in the long term. The fragmentation and alteration of the habitat can also affect the structure and social dynamics of the BLT family groups, making them seek alternative strategies to ensure reproduction and survival. In this work we investigated the structure and genetic diversity of L. chrysopygus, from fragments in two regions of current occurrence of the species, Pontal do Paranapanema and Alto Paranapanema; and we characterized the matrilineal structure and the kinship relations, with the aim of understanding socio-reproductive and demographic aspects, associated with historical and contemporary events, and thus generate relevant information for the management and conservation of the species. For this, analyses of microsatellites and the mitochondrial region Dloop were performed. The results show that the genetic diversity found in the fragments varied from low to moderate for both markers (Hd = 0.000 - 0.51; HO = 0.088 - 0.719). The predictive analysis revealed that only the population of Morro do Diabo (Pontal do Paranapanema), will be able to retain 90% of the current genetic diversity for the next 100 years. The historical demography analyses indicate a population reduction occurred approximately 5-7 thousand years ago, coinciding with the period of the Middle Holocene, when there were climatic and landscape changes in the Atlantic Forest. The kinship analyses suggest the occurrence of polygamy in some family groups of BLTs. The data generated in this work are relevant to increase the knowledge about the biology of the species, as well as to generate insights for its eventual management and conservation.
Genetic diversity, historical demography and socio-reproductive aspects of the black lion tamarin (Leontopithecus chrysopygus)
Keywords: Diversidade genética; Mata Atlântica; Primatas neotropicais; Marcadores moleculares; Genetic diversity; Atlantic forest; Neotropical primates; Molecular markers; CIENCIAS BIOLOGICAS::GENETICA